3D-printed Cu2O photoelectrodes for photoelectrochemical water splitting. Issue 12 (7th September 2020) - Ahn, Jinhyuck; Lee, Sanghyeon; Kim, Jung Hyun; Wajahat, Muhammad; Sim, Ho Hyung; Bae, Jongcheon; Pyo, Jaeyeon; Jahandar, Muhammad; Lim, Dong Chan; Seol, Seung Kwon
Abstract : Cu2 O 3D photoelectrode for PEC water splitting are realized by a sequential process including extrusion-based 3D printing and electrodeposition. Abstract : Photoelectrochemical (PEC) water splitting is an alternative to fossil fuel combustion involving the generation of renewable hydrogen without environmental pollution or greenhouse gas emissions. Cuprous oxide (Cu2 O) is a promising semiconducting material for the simple reduction of hydrogen from water, in which the conduction band edge is slightly negative compared to the water reduction potential. However, the solar-to-hydrogen conversion efficiency of Cu2 O is lower than the theoretical value due to a short carrier-diffusion length under the effective light absorption depth. Thus, increasing light absorption in the electrode–electrolyte interfacial layer of a Cu2 O photoelectrode can enhance PEC performance. In this study, a Cu2 O 3D photoelectrode comprised of pyramid arrays was fabricated using a two-step method involving direct-ink-writing of graphene structures. This was followed by the electrodeposition of a Cu current-collecting layer and a p–n homojunction Cu2 O photocatalyst layer onto the printed structures. The performance for PEC water splitting was enhanced by increasing the total light absorption area ( A a ) of the photoelectrode via controlling the electrode topography. The 3D photoelectrode ( A a = 3.2 cm 2 ) printed on the substrate area of 1.0 cm 2 exhibited a photocurrent ( I ph ) of −3.01 mA at 0.02 V ( vs. RHE), which is approximately three times higher than that of a planar photoelectrode with an A a = 1.0 cm 2 ( I ph = −0.91 mA). Our 3D printing strategy provides a flexible approach for the design and the fabrication of highly efficient PEC photoelectrodes.